Efficacy of the neurokinin‐1 receptor antagonist rolapitant in preventing nausea and vomiting in patients receiving carboplatin‐based chemotherapy. Issue 15 (13th May 2016) - Hesketh, Paul J.; Schnadig, Ian D.; Schwartzberg, Lee S.; Modiano, Manuel R.; Jordan, Karin; Arora, Sujata; Powers, Dan; Aapro, Matti
Abstract : BACKGROUND: Rolapitant, a novel neurokinin‐1 receptor antagonist, provided effective protection against chemotherapy‐induced nausea and vomiting (CINV) in a randomized, double‐blind phase 3 trial of patients receiving moderately emetogenic chemotherapy or an anthracycline and cyclophosphamide regimen. The current analysis explored the efficacy and safety of rolapitant in preventing CINV in a subgroup of patients receiving carboplatin. METHODS: Patients were randomized 1:1 to receive oral rolapitant (180 mg) or a placebo 1 to 2 hours before chemotherapy administration; all patients received oral granisetron (2 mg) on days 1 to 3 and oral dexamethasone (20 mg) on day 1. A post hoc analysis examined the subgroup of patients receiving carboplatin in cycle 1. The efficacy endpoints were as follows: complete response (CR), no emesis, no nausea, no significant nausea, complete protection, time to first emesis or use of rescue medication, and no impact on daily life. RESULTS: In the subgroup administered carboplatin‐based chemotherapy (n = 401), a significantly higher proportion of patients in the rolapitant group versus the control group achieved a CR in the overall phase (0‐120 hours; 80.2% vs 64.6%; P < .001) and in the delayed phase (>24‐120 hours; 82.3% vs 65.6%; P < .001) after chemotherapy administration. Superior responses were also observed by the measures of no emesis, no nausea, and complete protection in the overall and delayed phases and by the time to first emesis or use of rescue medication. The incidence of treatment‐emergent adverse events was similar for the rolapitant and control groups. CONCLUSIONS: Rolapitant provided superior CINV protection to patients receiving carboplatin‐based chemotherapy in comparison with the control. These results support rolapitant use as part of the antiemetic regimen in carboplatin‐treated patients. Cancer 2016;122:2418–2425 . © 2016 American Cancer Society . Abstract : The efficacy of rolapitant, a neurokinin‐1 receptor antagonist with a long duration of action, was examined in a subgroup of 401 patients with cancer who received carboplatin‐based chemotherapy in a phase 3 trial. In this population, a single oral dose of rolapitant (180 mg) combined with granisetron and dexamethasone provided statistically superior protection against chemotherapy‐induced nausea and vomiting in the delayed and overall phases in comparison with granisetron and dexamethasone alone, and it was well tolerated.